If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3m + 3 = m + -5 Reorder the terms: 3 + 3m = m + -5 Reorder the terms: 3 + 3m = -5 + m Solving 3 + 3m = -5 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. 3 + 3m + -1m = -5 + m + -1m Combine like terms: 3m + -1m = 2m 3 + 2m = -5 + m + -1m Combine like terms: m + -1m = 0 3 + 2m = -5 + 0 3 + 2m = -5 Add '-3' to each side of the equation. 3 + -3 + 2m = -5 + -3 Combine like terms: 3 + -3 = 0 0 + 2m = -5 + -3 2m = -5 + -3 Combine like terms: -5 + -3 = -8 2m = -8 Divide each side by '2'. m = -4 Simplifying m = -4
| 13x-7x+5x=-11 | | 8=4(3c+3) | | -10v=60 | | 2t-2=-2 | | 3x-3=2x-12 | | 5v^2+6v+7=v^2-4v | | 3d-12=-3 | | 0.4w-11=-0.5w | | 6+n=28+9 | | 2x+27=5x-3 | | r=50x-200 | | 188=-2x+4(6x-8) | | -8-3n=1 | | a+6=98 | | 3x+8=7x-12 | | 3x-2=2x-2 | | 98=7x+3(4x-18) | | 4c-6=3 | | x^2+20x= | | 0=.75x+75 | | -10x-10=-6x-30 | | 13x-4=6x+24 | | -y-15+9y=3y+2+4y | | 3w-18w=-60 | | 14=-(-6-8) | | 3x-r(x-1)=2(7-3x) | | 6(7n-4)-1=12+5n | | y=0.12x+17.52 | | 5x+72367=109917 | | 2x+1=2y+5 | | 1.25+a=2a+1 | | 7+2x=30 |